Is the Harrison-Zel'dovich spectrum coming back? ACT preference for ns ∼ 1 and its discordance with Planck. Issue 2 (9th March 2023) - Giarè, William; Renzi, Fabrizio; Mena, Olga; Di Valentino, Eleonora; Melchiorri, Alessandro
ABSTRACT: The Data Release 4 of the Atacama Cosmology Telescope (ACT) shows an agreement with an Harrison-Zel'dovich primordial spectrum ( ns  = 1.009 ± 0.015), introducing a tension with a significance of 99.3  per cent Confidence Level (CL) with the results from the Planck satellite. The discrepancy on the value of the scalar spectral index is neither alleviated with the addition of large scale structure information nor with the low multipole polarization data. We discuss possible avenues to alleviate the tension relying on either neglecting polarization measurements from ACT or in extending different sectors of the theory.